Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/mbio.00023-21
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Mitochondrion-Fatty Acid Axis for the Metabolic Reprogramming of Chlamydia trachomatis during Treatment with β-Lactam Antimicrobials

Abstract: Infection with the obligate intracellular bacterium Chlamydia trachomatis is the most common bacterial sexually transmitted disease worldwide. Since no vaccine is available to date, antimicrobial therapy is the only alternative in C. trachomatis infection. However, changes in chlamydial replicative activity and the occurrence of chlamydial persistence caused by diverse stimuli have been proven to impair treatment effectiveness. Here, we report the mechanism for C. trachomatis regulating host signaling processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…In previous studies, we demonstrated that FLIM of proteinbound NAD(P)H [τ 2 -NAD(P)H] in the inclusion can be used as an indicator for intracellular chlamydial metabolic activity (Szaszák et al, 2011;Käding et al, 2017;Shima et al, 2018Shima et al, , 2021. Therefore, we further analyzed τ 2 -NAD(P)H in chlamydial inclusions during treatment with DOX and AZM (Figures 1E,F).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In previous studies, we demonstrated that FLIM of proteinbound NAD(P)H [τ 2 -NAD(P)H] in the inclusion can be used as an indicator for intracellular chlamydial metabolic activity (Szaszák et al, 2011;Käding et al, 2017;Shima et al, 2018Shima et al, , 2021. Therefore, we further analyzed τ 2 -NAD(P)H in chlamydial inclusions during treatment with DOX and AZM (Figures 1E,F).…”
Section: Resultsmentioning
confidence: 98%
“…Either 2 μg/ml of DOX or 5 μg/ml of AZM inhibits C. trachomatis induced host metabolic activation as well as production of progeny, whereas C. trachomatis still survived and hence activated host metabolism under treatment with therapeutic serum concentration of AZM. Since C. trachomatis fundamentally needs host cell metabolites for its replication, it manipulates host cell glycolysis and mitochondria (Chowdhury et al, 2017;Shima et al, 2018Shima et al, , 2021Kurihara et al, 2019;Ende and Derré, 2020;Maffei et al, 2020;Rajeeve et al, 2020). Therefore, we suggest that the suppression of host metabolism enhanced by C. trachomatis is also an important factor for treatment of C. trachomatis infections.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations